Pengaruh globalisasi terhadap proses gender mainstreaming di Malaysia - Ismail, Nur Syakiran Akmal (2013)
The participation of women in all spheres of life has been accelerated by strategies such as gender mainstreaming. Gender mainstreaming, which was launched in 1995 at the Fourth World Conference on Women in Beijing, is a global strategy used to promote gender equality.It refers to the process of assessing the implications for women and men of any planned action, including legislation, policies or programs, in all areas and at all levels.The implementation of Gender Mainstreaming was suggested to all countries as a toll to achieve gender equality globally.Based on late literatures, it is shown that the process of Gender Mainstreaming was practised before the concept was introduced.Therefore, this paper will explain the process of Gender Mainstreaming in Malaysia since independence using content analysis method.The result revealed that the process of gender mainstreaming in Malaysia has been dominantly influenced by local women activist as well as international activist.